Mass spectrometric study of rhamnolipid biosurfactants and their interactions with cell membrane phospholipids - Pashynska, V.A. (Вiopolymers and Cell, 2009)
Aim. To examine the formation of supramolecular complexes of biogenous rhamnolipids with membrane phospholipids that is considered as a molecular mechanism of the biosurfactants antimicrobial action. Methods. In the present work rhamnolipid biosurfactant samples produced by Pseudomonas sp. PS-17 strain have been investigated by electrospray ionization mass spectrometry for the first time. Results. As a result of the study, characteristic mass spectra of the rhamnolipid samples were obtained, that can be used as reference spectra for mass spectrometric identification of the compounds in any biological or industrial samples. At the next stage of the experiments the pair systems, containing the biosurfactants and a membrane phospholipid dipalmitoylphosphatidylcholine, have been tested. The cationized noncovalent complexes of the rhamnolipids with the phospholipid were observed in the spectra. Conclusions. The results obtained testify to the consideration that rhamnolipids (similar to other membranotropic agents) can form stable supramolecular complexes with membrane phospholipids that are able to evoke the biosurfactants antimicrobial action. A great potential of electrospray ionization mass spectrometry for the biosurfactants identification and study has been demonstrated in the work.